Renar Bibit's leadership model based from Davao Crocodile Park's internal communication strategies - Repollo, Alnessa Mhea V.
This paper uses a qualitative descriptive study as a design of the research. Quantitative data were also utilized for a better assessment of the research. The researcher conducted an interview with the manager, survey with the employees, and actual observation in one of their meetings. This study generally aims to know the leadership style of the manager and how it affects the company's internal communication. This study also aims to present a model of the kind of leadership the manager has and how it effectively move the company's internal resources-employees. This study aspires to identify the leadership style of the operations manager of Davao Crocodile Park, Mr. Renar Bibit, through their internal communication strategies. The primary respondent of this study is Mr. Renar Bibit. However, the employees were also asked to answer a survey questionnaire to rate their Work Satisfaction, Morale, Motivation, and Leadership Effectiveness after such communication strategies were implemented. The manager has a clear concept of what leadership is. This concept involves a goal and tasks to attain the goal. This concept is also translated to the internal members of the organization who are the employees with the use of formal and informal communication tools. These tools created upward, downward, and horizontal communication works. The communication strategies which offer informality also formed an idela supportive climate. Mr. Renar Bibit's leadership style generally falls on the ?participative-group? kind of leadership. It is the system four of Rensis Likert's management style which is close to the ideal. This style encompasses supportive relationships, participatory decision-making, enhanced morale and motivation, and absolute teamwork. The leadership model created for Mr. Renar Bibit shows the process of leadership and how this affected the communication strategies in the organization and the effect towards the employees' work satisfaction, morale, and self-control. Overall, the employees feel confidence in the management of their leader, are generally happy with their work, and improved self-esteem and self-control. This study proved that leadership is not a one-way process where it only depends on the manager's capability or intelligence. It is a process where both the manager and the employees work together towards a vision for the company. In this study, informality helps in the environment of the Davao Crocodile Park. However, it is not proven in this study that this also works to other business environments. Thus, the researcher recommends further study on leadership styles in different contexts such as small and medium enterprises
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication